2018
DOI: 10.1136/bmjopen-2018-023532
|View full text |Cite
|
Sign up to set email alerts
|

Protection of pregnant women at work in Switzerland: practices, obstacles and resources. A mixed-methods study protocol

Abstract: IntroductionLike most industrialised countries, Switzerland has introduced legislation to protect the health of pregnant workers and their unborn children from workplace exposure. This legislation provides for a risk assessment, adaptations to workplaces and, if the danger is not eliminated, preventive leave (prescribed by a gynaecologist). This study’s first objective is to analyse the degree to which companies, gynaecologists and midwives implement the law. Its second objective is to understand the obstacles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This study was part of a broader research project (Krief et al, 2018) investigating the application of maternity protection measures in Switzerland. In the project's initial phase, managers of 107 healthcare institutions answered a telephone questionnaire investigating their implementation of the OProMa (Abderhalden-Zellweger et al, 2021).…”
Section: Participant Selection and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was part of a broader research project (Krief et al, 2018) investigating the application of maternity protection measures in Switzerland. In the project's initial phase, managers of 107 healthcare institutions answered a telephone questionnaire investigating their implementation of the OProMa (Abderhalden-Zellweger et al, 2021).…”
Section: Participant Selection and Data Collectionmentioning
confidence: 99%
“…Switzerland has also passed specific legislation to protect the health of pregnant employees while enabling them to continue their professional activities (see Section 1.3). Proper implementation of the measures provided for by these pieces of legislation would not only efficiently protect pregnant workers from several of the risks that they face (Croteau, Marcoux, & Brisson, 2006) but also reduce rates of absenteeism during pregnancies (Kristensen et al, 2008;Pedersen et al, 2020). Several studies have identified organizations' shortcomings in the implementation of maternity protection measures, including the absence of a risk assessment and the absence, or inadequacy, of workplace accommodation (Adams et al, 2016a(Adams et al, , 2016bLembrechts & Valgaeren, 2010;Rudin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of French-speaking Switzerland, a recent study carried out in two occupational sectors shows that only 12% of workers in the health sector and 2% in the food industry benefit from the protection in accordance with the Swiss legislation [9]. Companies apply the legislation in a heterogeneous/partial manner and gynecologists dot not always feel competent in occupational health issues to assess the hazardousness of working conditions of pregnant women [5,[9][10][11]. At the international level, publications underline the heterogeneous applications of the legislations surrounding maternity protection at work.…”
Section: Introductionmentioning
confidence: 99%